Wait for me - Warren, Susan May, 1966- (Warren, Susan May, 1966- Montana rescue., 2018)
"When two women go missing in the Montana wilderness, Pete Brooks must trust his skills, teammates--and the woman who broke his heart--if he hopes to bring them all home alive."--